GREEN ENERGY TRANSITIONS: CONGO'S 'MODERN-DAY SLAVERY' IN RAW MATERIALS DEMANDS - Zulkarnain, Muhammad Fitrah; Paksi, Arie Kusuma (Sanata Dharma University, 2025)
The Democratic Republic of the Congo (DRC), a country rich in cobalt and coltan—two elements necessary for renewable technologies—has come under greater investigation as a result of the worldwide shift to green energy, yet its miners are exploited. This qualitative study, which was based on the resource curse and human security theories, used document analysis of previous studies, policy reports, and current events to examine the conflicting reality of resource exploitation in the Democratic Republic of the Congo and the aspirations for green energy. The results show that although programs encouraging ethical production and responsible sourcing have promise, structural problems like child labor, forced labor, and dangerous working conditions still exist and threaten the fundamental safety and dignity of local people. In order to guarantee that the DRC's resource richness promotes equitable development rather than exploitation, this study highlights the necessity of international accountability systems and moral behavior that places a higher priority on human security and dignity.